Caracterização fisica, fisico-química e enzimática de frutos de seis cultivares de coqueiro anão em diferentes estadios de desenvolvimento. - Maciel, Vlayrton Tomé (2008)
This study aimed at characterizing in fruit and physico-chemical, and sensory enzyme in the coconut water the of six dwarf coconut cultivars at seven stages of development. The studied cultivars were: Green dwarf from Jequi (GDJ), yellow dwarf from Gramame (YDG), yellow dwarf from Malaysia (YDM), Red dwarf from Cameroon (YDC), Red dwarf from Malaysia (RDM), Red dwarf from Gramame (RDG). Fruits were harvested from an experimental field, Embrapa Meio Norte (Parnaiba city, Piauí State), at the following stages of development: 126, 147, 168, 189, 210, 231, and 252 days after the opening of the inflorescences. Upon harvest, fruits were taken to the Laboratory of Postharvest physiology and technology at Embrapa Agroindustria Tropical, located in Fortaleza, Ceará, were the physical and physic-chemical analyses were performed. Part of the samples were stored at -85°C and then transported to the Laboratory of Plant Physiology, Biochemistry and Molecular Biology Department from The Federal University of Ceará, were the enzymatic study was conducted. The experimental designed was a completely randomized one in a factorial scheme 6 x 7. First physical characterization (mass, length, diameter, water volume, and color of the shell) was individually performed for each fruit, then the physic-chemical analyses of coconut water: total soluble solids (TSS), total soluble sugar (TSSu), reducing sugars (RS), total titratable acidity (TTA), sugar to acid ratio (TSS/TTA), pH, turbidity, and protein. It was also evaluated the activities of enzymes that oxide phenols [polyphenoloxidase (PFO) and peroxidase specific for the guaiacol (G-POD)], as well as those of the cycle of ascorbate-glutathione [superoxide dismutase (SOD), catalase (CAT) and the ascorbate peroxidase (APX). Moreover some of the sensory aspects of the water were evaluated. The results showed that the YDR, YDG, and RDG may be commercially exploited, due to their physical and physic-chemical characteristics. It was also concluded that, the best time for harvesting is somewhat between 189 to 210 days after fruit developed set, since right at this time the studied cultivars presented the best quality attributes. There was detected activity of G-POD in the coconut water from any of the cultivars. The activity of SOD in the coconut water increased in the early stages of development of the fruits of all the cultivars, such as RDG and YDG cultivars such as those that showed higher enzyme activity. A CAT proved to be the main enzyme eliminating of hydrogen peroxide of coconut water and its activity varied greatly it the development of the fruit and also between the cultivars.